Autonomy or interdependence in distributed systems - Schroeder, Mike (Proceedings of the 3rd workshop on ACM SIGOPS European workshop: Autonomy or interdependence in distributed systems?, 1988)
You want your own processors and memory because 1) you want administrative control over its scheduling policy and 2) having your own makes it potentially more private. Having administrative control means you can optimize for low latency rather than high throughput and that you can be sure to have computing at 2am Monday morning as well as at 2pm Thursday afternoon. If you are not careful, having administrative control turns you into a "system manager", a very unpleasant prospect if the system is, say, Unix; not that much better if i t ' s a Macintosh (installing new software and I/O devices is time consuming and mysterious). One strong argument for interdependent systems is that a site can hire a single system manager to manage all workstations. But he will only be able to do that if they all use a fairly standard configurations of hardware and software. Even if they all run "stand-alone", the common management reduces autonomy. You don't ever want your own name server, file server or authenticate.